Spreading online rumours during the COVID-19 pandemic: the role of users' knowledge, trust and emotions as predictors of the spreading patterns. Issue 2 (3rd July 2022) - Weimann-Saks, Dana; Elshar-Malka, Vered; Ariel, Yaron; Weimann, Gabriel
ABSTRACT: The COVID-19 pandemic has generated severe social, economic, and political implications and challenges in addition to unprecedented health threats and harm. A typical phenomenon associated with emergencies and crises is the spreading of rumours. Social networks have become a popular arena for spreading rumours in various contexts, including during the COVID-19 pandemic. This study analysed the circumstances under which people might spread such rumours and the psychological mechanism behind this behaviour. We examined potential factors that might influence the spreading of pandemic-related online rumours (behavioural component): the participants' thoughts and beliefs about the rumour (cognitive component), users' trust in the information to which they are exposed by the media (trust component), and the emotional response to information regarding the epidemic resulting from media exposure (emotional component). Using a survey of individuals who were exposed to COVID-19 rumours, we could test the effects of our independent variables on the willingness to spread the rumours. Research findings indicate that there is a correlation between the cognitive component and the behavioural component. We also identified a mediated route of influence through the trust component. Contrary to our hypothesis, we didn't find that the emotional component was a mediator between the cognitive and behavioural components.